MODEL BISNIS KELOMPOK USAHA MADU LINOT DI KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Dedy Darmansyah; Yoga Nugroho (Universitas Teuku Umar, 2021)
In conducting business development, the Business Group must know how the business model is being run in business development efforts. The business model reflects strategic choices and operational implications that help companies to communicate, analyze, test and validate a causal relationship stemming from the strategic choices made (Shafer et al. 2005 in Wiska 2016). The potential owned by the group of linot honey cultivation business still can not be maximized by members of the group. This is seen by the market conditions of the product group of linot honey cultivation business group is still not developed compared to the market owned by the Business Group of linot honey cultivation located in other provinces. This is in accordance with the results of research by Sarma Year 2010 which shows that entrepreneurial behavior has an influence on the success of a company run. One of them is the innovative attitude of the company's actors. Then the Business Group must map the current business model. The research was conducted in business model mapping with Business Model Canvas (BMC) method.